Stabilization of Carbenes via α-Ylide Substitutions: A Computational Quest for New Divalents at DFT - Narjes Haerizade, Bibi; Zaman Kassaee, Mohammad; Koohi, Maryam; Ghavami, Monire; Zandi, Hassan (Combinatorial Chemistry & High Throughput Screening, 2014)
In our continued quest for novel stable carbenes, silylenes, and germylenes, here we compare and contrast multiplicities and relative stabilities of carbenes affected with four different α-ylides. The latter include carbon, immonium, phosphorus, and sulfur ylides substituted at the alpha positions of carbenes with acyclic, cyclic and cyclicunsaturated structural frameworks. Related thermodynamic data are calculated at B3LYP/6-311++G**//B3LYP/6-31+G* and B3LYP/AUG-cc-pVTZ//B3LYP/6-31+G* levels. Investigations reveal the enlargement of the singlet-triplet energy gaps (ΔΕs-t) in the order of immonium > phosphorus > sulfur > carbon. The observed trend, which is taken as an indication of stability, is thoroughly analyzed by applying appropriate isodesmic reactions which differentiate the substituent effects on each of our singlet or triplet carbene. The effect of unsaturation is also probed in each series of the ylide carbenes. The reactivity of the species is discussed in terms of nucleophilicity and electrophilicity.
Keywords: carbene